Genomic analysis of the diversity, antimicrobial resistance and virulence potential of clinical Campylobacter jejuni and Campylobacter coli strains from Chile. - Veronica Bravo; Assaf Katz; Lorena Porte; Thomas Weitzel; Carmen Varela; Narjol Gonzalez-Escalona; Carlos J Blondel (Public Library of Science (PLoS), 2021)
Campylobacter jejuni and Campylobacter coli are the leading cause of human gastroenteritis in the industrialized world and an emerging threat in developing countries. The incidence of campylobacteriosis in South America is greatly underestimated, mostly due to the lack of adequate diagnostic methods. Accordingly, there is limited genomic and epidemiological data from this region. In the present study, we performed a genome-wide analysis of the genetic diversity, virulence, and antimicrobial resistance of the largest collection of clinical C. jejuni and C. coli strains from Chile available to date (n = 81), collected in 2017-2019 in Santiago, Chile. This culture collection accounts for more than one third of the available genome sequences from South American clinical strains. cgMLST analysis identified high genetic diversity as well as 13 novel STs and alleles in both C. jejuni and C. coli. Pangenome and virulome analyses showed a differential distribution of virulence factors, including both plasmid and chromosomally encoded T6SSs and T4SSs. Resistome analysis predicted widespread resistance to fluoroquinolones, but low rates of erythromycin resistance. This study provides valuable genomic and epidemiological data and highlights the need for further genomic epidemiology studies in Chile and other South American countries to better understand molecular epidemiology and antimicrobial resistance of this emerging intestinal pathogen.